Socio-spatial cognition in cats: Mentally mapping owner's location from voice. - Saho Takagi (Public Library of Science (PLoS), 2021)
Many animals probably hold mental representations about the whereabouts of others; this is a form of socio-spatial cognition. We tested whether cats mentally map the spatial position of their owner or a familiar cat to the source of the owner's or familiar cat's vocalization. In Experiment 1, we placed one speaker outside a familiar room (speaker 1) and another (speaker 2) inside the room, as far as possible from speaker 1, then we left the subject alone in the room. In the habituation phase, the cat heard its owner's voice calling its name five times from speaker 1. In the test phase, shortly after the 5th habituation phase vocalization, one of the two speakers played either the owner's voice or a stranger's voice calling the cat's name once. There were four test combinations of speaker location and sound: SamesoundSamelocation, SamesoundDifflocation, DiffsoundSamelocation, DiffsoundDifflocation. In line with our prediction, cats showed most surprise in the SamesoundDifflocation condition, where the owner suddenly seemed to be in a new place. This reaction disappeared when we used cat vocalizations (Experiment 2) or non-vocal sounds (Experiment 3) as the auditory stimuli. Our results suggest that cats have mental representations about their out-of-sight owner linked to hearing the owner's voice, indicating a previously unidentified socio-spatial cognitive ability.